Semiotic Examination of Algebra Teaching Process in the Context of Gestures - Dilek Tanışlı; Şahin Danişman (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This research aims to examine the gestures used by teachers and students in the algebra learning-teaching process and the purpose of these signs. The participants of this case study are 25 eigth graders and their mathematics teacher. The data were collected through video recordings and clinical interviews. Deductive analysis was used to analyze the data, while synchronic and diachronic analyses were utilized to analyze the signs in terms of semiotics. Findings revealed that the teacher used a bunch of iconic, metaphoric, deictic, and beat gestures during the algebra teaching process. The meaning of the iconic gestures that resulted in the study can be listed as centering and itemization, illustration of a table, constant term, preceding element, decrease, separation, base and power, rectangle and side, length, and vertical-horizontal. On the other hand, the metaphorical gestures attribute holding, equality, moving the term from one side to the other, numbers or letters, equality, distributing and hiding. The deictic gestures imply pointing out boards with fingers, board markers or hands, and indicating students and notebooks with fingers, while the beat gestures refer to lowering the hands from top to bottom, waving the fist up and down and moving the hand back and forth. It is seen that the teacher aims to strengthen her expression and support students' mathematical understanding through the gestures she uses.